DNA adduct formation and mutation induction by aristolochic acid in rat kidney and liver - Mei, Nan; Arlt, Volker M; Phillips, David H; Heflich, Robert H; Chen, Tao (Mutation Research-Fundamental and Molecular Mechanisms of Mutagenesis, 2006)
Aristolochic acid (AA) is a potent nephrotoxin and carcinogen and is the causative factor for Chinese herb nephropathy. AA has been associated with the development of urothelial cancer in humans, and kidney and forestomach tumors in rodents. To investigate the molecular mechanisms responsible for the tumorigenicity of AA, we determined the DNA adduct formation and mutagenicity of AA in the liver (nontarget tissue) and kidney (target tissue) of Big Blue rats. Groups of six male rats were gavaged with 0, 0.1, 1.0 and 10.0 mg AA/kg body weight five times/week for 3 months. The rats were sacrificed 1 day after the final treatment, and the livers and kidneys were isolated. DNA adduct formation was analyzed by 32P-postlabeling and mutant frequency (MF) was determined using the lambda Select-cII Mutation Detection System. Three major adducts (7-[deoxyadenosin-N6-yl]-aristolactam I, 7-[deoxyadenosin-N6-yl]-aristolactam II and 7-[deoxyguanosin-N2-yl]-aristolactam I) were identified. There were strong linear dose-responses for AA-induced DNA adducts in treated rats, ranging from 25 to 1967 adducts/10(8) nucleotides in liver and 95-4598 adducts/10(8) nucleotides in kidney. A similar trend of dose-responses for mutation induction also was found, the MFs ranging from 37 to 666 x 10(-6) in liver compared with the MFs of 78-1319 x 10(-6) that we previously reported for the kidneys of AA-treated rats. Overall, kidneys had at least two-fold higher levels of DNA adducts and MF than livers. Sequence analysis of the cII mutants revealed that there was a statistically significant difference between the mutation spectra in both kidney and liver of AA-treated and control rats, but there was no significant difference between the mutation spectra in AA-treated livers and kidneys. A:T-->T:A transversion was the predominant mutation in AA-treated rats; whereas G:C-->A:T transition was the main type of mutation in control rats. These results indicate that the AA treatment that eventually results in kidney tumors in rats also results in significant increases in DNA adduct formation and cII MF in kidney. Although the same treatment does not produce tumors in rat liver, it does induce DNA adducts and mutations in this tissue, albeit at lower levels than in kidney.